Gamification element through massive open online courses in TVET: an analysis using analytic hierarchy process - Mohd Yusoff, Azizul; Salam, Sazilah; Mohamad, Siti Nurul Mahfuzah; Daud, Rafizah (American Scientific Publishers, 2017)
MOOC stands for Massive Open Online Course which is an online course aimed at unlimited participation and open access via the web. In this paper, we present a study to determine the best gamification mechanics suitable for Technical and Vocational Education and Training (TVET) learning since various TVET providers’ lack of competencies in identifying and significant applicable and current vocational pedagogic competence for Twenty Fist Century TVET. Gamification is the integration of game-like design elements into non-game context to engage learners as well as function as entertainment that cause learners to enjoy actively participating and engaging with others, such as through reputation points, rewards and goal setting. In tertiary education, researchers and practitioners have been search for effective techniques to improve student engagement and stimulate learning. The study involved 36 students from TVET Public University (Level 6) and 34 students from TVET Community College (Level 3) as a sample. The results revealed that for TVET Level 6 learner’s preferred Learner–Content interaction (0.4488) while TVET Level 3 learners preferred Learner–Instructor interaction (0.4652). The best six of gamification mechanic for each gamification interaction criterion were selected based on the highest weight for each criterion. For Group 1 which is Rewards (0.4135), Skill Points (0.3279), Trophies-Badges (0.3101), Wally Games (0.3021), Progress Bar (0.2765) and Virtual Goods (0.2587). While for Group 2 are Rewards (0.5779), Memory Game (0.4454), Team Leader Board (0.2508), Redeemable Point (0.2440), Progress Bar (0.2329) and Peer Emotion Feedback (0.2074).